Determinación de los niveles de ruido ambiental en las prestadoras de servicios médicos (IESS, Hospital General, Clínicas) para realizar programas de mitigación en el cantón Latacunga, Cotopaxi, período 2013 - Vargas Sarabia, Santiago David (2014)
In the Latacunga city medical health centers are mostly nowadays in the downtown, in addition they are interfered by the principals rues of vehicle roads with expansion of the population and the increase of different kinds of transportation such as private cars, public vehicles and freight vehicles. The environmental impact is represented in the contribution of pollution about daily environmental noise levels which we are generated vehicular circularity. Vehicular movement of public transportation is one of the main contaminants or pollutants of environmental noise that cause traffic in the streets, that encourage drivers of vehicles to make sound their horns, giving rise to a chain reaction of multiple sounds between horns, noisy and desperate acceleration of their engines. Causing trouble and damage, producing psychological and social changes.Affecting the passers and especially the patients that are interned in the medical health centers in the city.